Video Education Reduces Pain and Anxiety Levels in Cancer Patients Who First Use Fentanyl Transdermal Patch: A Randomized Controlled Trial - Ye Z; Chen J; Zhang Y; Hu X; Xuan Z; Yang S; Mao X; Rao Y (Dove Medical Press, 2020)
Ziqi Ye,1,* Jie Chen,2,* Yanfang Zhang,1 Xi Hu,1 Zixue Xuan,3 Si Yang,1 Xiaohong Mao,3 Yuefeng Rao1 1Department of Clinical Pharmacy, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 3Department of Pharmacy, Zhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuefeng Rao Department of Clinical PharmacyThe First Affiliated Hospital, Zhejiang University School of Medicine, 79 Qingchun Road, Hangzhou 310003, People’s Republic of ChinaTel +86-571-8723-6531Email raoyf@zju.edu.cnXiaohong Mao Department of PharmacyZhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, 158 Shangtang Road, Hangzhou 310014, People’s Republic of ChinaTel +86-15990151723Email maoxhzhz@163.comObjective: We sought to evaluate the efficacy of using a quick response (QR) code within video education to guide proper use of fentanyl transdermal patches and control pain, depression, and anxiety levels in cancer patients.Methods: Patients using a fentanyl transdermal patch for the first time were enrolled in the study and then given an information leaflet as well as an informed consent form. We asked them to complete the first questionnaire (Q1) prior to first use of the fentanyl transdermal patch, and then used a random number table to randomize those who completed it into two groups. Participants in group A received a QR code (to make it easier for them to obtain additional video information) and a traditional information leaflet, whereas those in group B (control group) only received a traditional information leaflet. Thereafter, we requested all participants to complete standard questionnaires, which comprised a Numeric Rating Scale (NRS), a Spielberger State-Trait Anxiety Inventory (STAI), as well as a Hospital Anxiety and Depression Scale (HADS). The resulting continuous (with a normal distribution) and categorical data were analyzed using Student’s t- and chi-square tests, respectively. We also recorded parameters such as NRS, STAI, and HADS, as well as the frequency of rescue medication in both groups.Results: A total of 154 cancer patients who first used a fentanyl transdermal patch were recruited during the study period, from April to May 2020. Among these, 138 completed follow-up, with 70 and 68 in group A and B, respectively. Participants in both groups had similar baseline and clinical characteristics, whereas significant differences were observed between the groups with regard to the other parameters. Specifically, participants in group A recorded a lower STAI state (38.2 vs 38.9, P=0.027) and HADS (3.9 vs 4.2, P=0.001) anxiety scores, as well as NRS (2.1 vs 2.4, P=0.025) and frequency of rescue medication (0.4 vs 1.4, P< 0.001) than those in group B, following 14 days of using a fentanyl transdermal patch.Conclusion: Our results indicated that incorporating a QR code within additional video education leads to proper use of a fentanyl transdermal patch and relieves pain and anxiety levels in patients with cancer. Based on this, we recommend a new style of education during care of cancer patients who first use a fentanyl transdermal patch.Keywords: QR code, video education, fentanyl transdermal patch, anxiety, depression